The Influence of Islamic Work Ethics, Despotic Leadership and Helpful Behavior on the Performance of Individuals with Gender as Moderation Study at Bank Syariah Indonesia Slamet Riyadi Branch - Fadhila Nur Widowati; Asri Laksmi Riani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to study the causal relationship between Islamic Work Ethics, Despotic Leadership and Helpful Behavior on the Performance of Individuals with Gender as a Moderating Study at Bank Syariah Indonesia Slamet Riyadi 01 Branch. The population in this study is the total employees at Islamic banks in the city of Surakarta which amounts to approximately 300 people. The sample used in this study used calculations from (Joseph F Hair et al., 2010) which the number of samples was five times the number of indicators, so that the number of samples used was 230 people. The results of this study explain that Islamic business ethics have a significant and significant effect on depostic leadership, despotic leadership has an indirect and significant effect on helping behavior through despotic leadership, Despotic leadership has an indirect effect on individual performance through helping behavior, Gender moderation has a significant effect on despotic leadership. Keywords: Islamic Work Ethics, Despotic Leadership, Helpful Behavior, Performance of Individuals with Gender